Cognitive development of term small for gestational age children at five years of age. Issue 1 (1st July 2000) - Sommerfelt, K; Andersson, H W; Sonnander, K; Ahlsten, G; Ellertsen, B; Markestad, T; Jacobsen, G; Hoffman, H J; Bakketeig, L
Abstract : AIM: To assess the relative significance for cognitive development of small for gestational age, parental demographic factors, and factors related to the child rearing environment. METHODS: IQ of a population based cohort of 338 term infants who were small for gestational age (SGA) and without major handicap, and a random control sample of 335 appropriate for gestational age (AGA) infants were compared at 5 years of age. RESULTS: The mean non-verbal IQ was four points lower, while the mean verbal IQ was three points lower for the children in the SGA group. The results were not confounded by parental demographic or child rearing factors. However, parental factors, including maternal non-verbal problem solving abilities, and child rearing style, accounted for 20% of the variance in non-verbal IQ, while SGA versus AGA status accounted for only 2%. The comparable numbers for verbal IQ were 30 and 1%. Furthermore, we found no evidence that the cognitive development of SGA children was more sensitive to a non-optimal child rearing environment than that of AGA children. Maternal smoking at conception was associated with a reduction in mean IQ comparable to that found for SGA status, and this effect was the same for SGA and AGA children. The cognitive function of asymmetric SGA was comparable to that of symmetric SGA children. CONCLUSIONS: Our findings indicate that child cognitive development is strongly associated with parental factors, but only marginally associated with intrauterine growth retardation.